2018
DOI: 10.1002/jcb.27284
|View full text |Cite
|
Sign up to set email alerts
|

Long noncoding RNA TUG1 promotes cell proliferation and migration of renal cell carcinoma via regulation of YAP

Abstract: Our findings indicated a pivotal role of TUG1 in driving RCC progression via regulation of miR-9/YAP, suggesting a potential therapeutic targeting role of TUG1 in RCC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(32 citation statements)
references
References 39 publications
2
30
0
Order By: Relevance
“…23 Previous studies have reported that LINC00339 is the sponge for miR-377-3p, miR-145, and miR-539-5p. [12][13][14] This work for the first time identified LINC00339 as the sponge for miR-1182. To date, knowledge about miR-1182 is poor.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…23 Previous studies have reported that LINC00339 is the sponge for miR-377-3p, miR-145, and miR-539-5p. [12][13][14] This work for the first time identified LINC00339 as the sponge for miR-1182. To date, knowledge about miR-1182 is poor.…”
Section: Discussionmentioning
confidence: 81%
“…21 Recently, several researchers have demonstrated that LINC00339 promotes proliferation, migration, and invasion of laryngeal squamous cell carcinoma and breast cancer. 13,14 Its role in HCC remains limitedly studied. We provided evidence that LINC00339 promotes HCC tumorigenesis and metastasis through the miR-1182/ SKA1 pathway.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…30 A study has showed that downregulated lncRNA taurine-up-regulated gene 1 (TUG1) occurs with decreased YAP levels. 31 A new study has noted that Beclin1 works in autophagy via complexes like the Beclin1-PI3KC3 or Beclin1-Bcl-2 complex. 32 LC3II was considered as an autophagy-linked marker in cell tissues.…”
Section: Discussionmentioning
confidence: 99%
“…LncRNA THOR mediated the progression of retinoblastoma through regulating c-myc and IGF2BP1 [18] . In addition, TUG1 has been reported to target YAP to regulate cell proliferation and migration of renal cell carcinoma [19] . In the present study, our result revealed that TUG1 mediated periprosthetic osteolysis by directly targeting BMP-7.…”
Section: Discussionmentioning
confidence: 99%